Somalia : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Somalia. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Context: Somalia is a fragile state emerging from a protracted civil war. In 1991, the government was toppled by armed opposition groups, leading to implosion of the central government and devolution of power to administrative regions. The Fund recognized the Federal Government of Somalia on April 12, 2013, paving the way for staff to provide policy advice and technical assistance. While Somalia has been welcomed back as an active member of the Fund, it remains ineligible for financial assistance pending the clearance of its longstanding arrears. The political and security situation remains challenging. Complex clan politics and high turnover in the members of the economic team have undermined policymaking. A new government took office on February 18, 2015, and presidential elections are planned for September 2016. Key policy issues: The Article IV discussions focused on immediate and medium-term actions for building institutions and policy frameworks for fiscal and financial management. Specifically, -- Capacity building and governance. Concerted action is needed to build institutions and improve governance in order to support sustainable, inclusive growth, and poverty reduction. In particular, urgent efforts are required to set in place sound mechanisms and institutions to ensure that prospective natural resource wealth, notably hydrocarbons, is well managed. Considerable donor assistance is required for helping Somalia to meet these daunting challenges. -- Fiscal. Decisive steps are necessary to build fiscal discipline, underpinned by realistic budgeting and effective implementation systems, including commitment controls. The 2015 budget needs to be revised in light of revenue shortfalls. An emergency revenue mobilization plan and an expenditure review are warranted. -- Financial sector. Efforts are needed to develop the currently rudimentary financial system. Swift action is required so that remittances can be channeled through the international banking system. Currency reform should not be implemented until prerequisites are in place. Given the extent of dollarization and the absence of monetary policy instruments, the central bank is unable to conduct monetary policy. Past IMF advice: The latest Article IV consultation was on November 13, 1989, and focused on the low priority attached by the government in place then on the need for better controlling unproductive spending, and on the need for better economic and social services.